Body composition and bone mineral density of Division 1 collegiate football players: A consortium of college athlete research study. - Bosch, T. A.; Carbuhn, A. F.; Stanforth, P. R.; Oliver, J. M.; Keller, K. A.; Dengel, D. R. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to generate normative data for total and regional body composition in Division 1 collegiate football players using dual-energy x-ray absorptiometry (DXA) and examine positional differences in total and regional measurements. Data were used from the Consortium of College Athlete Research (C-CAR) group. Four hundred sixty-seven players were included in this study. Height, body mass, total and regional fat mass, lean mass, and bone mineral density were measured in each athlete in the preseason (June-August). Players were categorized by their offensive or defensive position for comparisons. Linemen tended to have the higher fat and lean mass measures (p = 0.05 for all) compared with other positions. Positions that mirror each other (e.g. linemen) had similar body composition and body ratios. All positions were classified as overweight or obese based on body mass index (BMI) (>25 kg·m-2), yet other than offensive and defensive linemen, all positions had healthy percent body fat (13-20%) and low visceral fat mass (<500 g). The data presented here provide normative positional data for total and regional fat mass, lean mass, and bone density in Division 1 collegiate football players. Player position had a significant effect on body composition measures and is likely associated with on-field positional requirements. From a player's health perspective, although all positions had relatively high BMI values, most positions had relatively low body fat and visceral fat, which is important for the health of players during and after their playing career. The increased accuracy and reliability of DXA provides greater information, regarding positional differences in college football players compared with other methods.